Program Kemitraan Masyarakat Kelompok Usaha Pembuatan Nugget Melalui Pelatihan Kewirausahaan, Digital Marketing dan Pelatihan Penggunaan Alat Pada Era Normal Baru di Paninggilan Tangerang Banten - Anwar Rifa’I; Prita Andini; Hadidtyo Wisnu Wardani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This community partnership program focuses on using digital technology with utilize digital technology and information to help develop MSMEs in food sector. The partner in this activity is MSME Nugget which currently still has limitations in terms of production, management, and marketing. The purpose of the activity partnership to the community is to provide solutions to challenges that owned by MSME nuggets by carrying out activities that are able to empower employees of MSMEs. The method used is to conduct observations and interviews with the chairman and the entire business management team. The solution offered to overcome the problem of low production is by developing production support equipment consisting of meat grinders, machines steamers, and nuggets fryers and also delivering how to use those equipment training. The solution to the problem of untidy MSME management is by delivering entrepreneurship training. Meanwhile, solutions for marketing what is still limited is providing training on the use of social media and marketplaces and using strong branding on products. It is hoped that the implementation of this solution will have a positive impact on MSMEs. Impact related to production problems is increasing production to 6 times, related to management is the availability of a neat management and related marketing is increasing the reach of marketing to become wider.